Quand le droit pense la politique : à propos de deux lettres d’al-Muḫtār al-Ṣaġīr al-Kuntī (m. 1847) à l’imam de Ḥamdallāhi - Ismail Warscheid (Afriques)
This article examines two letters sent by the head of the Kunta family in the Azaouad region, al-Muḫtār al-Ṣaġīr al-Kuntī (d. 1847), to Aḥmad Lobbo (d. 1845) at the time of the Ḥamdallāhi imamate’s expansion into the Niger Bend during the 1830s. The aim is to investigate how the science of law in Islam (fiqh) acts as a versatile tool of political communication that intervenes directly in local power relations. On the one hand, I analyze how Islamic contractual mechanisms affected the management of conflictual relations between lineage groups. On the other, I shed light into a more global process of juridification of politics in the region perceptible in both letters. Al-Muḫtār al-Ṣaġīr envisions Ḥamdallāhi’s conquest of the Niger Bend essentially through a conceptual framework forged by Muslim jurists after the tenth century to lay down the institutional foundations of public order, beginning with the judiciary (al-qaḍāʾ). By exploring this performative dimension of Muslim scholarly discourses, I hope to provide new insights into the question of how the spread of Islamic law and literacy reconfigured social, cultural, and political interaction in post-1400 Sahelo-Saharan societies.